Advertising agency retention: Views from South African advertisers - M. Jansen Van Rensburg; P. Venter; J. W. Strydom (South African Journal of Business Management, 2009)
Commercial reality demands long and lasting relationships that are beneficial to both advertising agencies and their clients. This article presents a conceptual model to illustrate the salient choice criteria employed by advertisers when renewing advertising agency contracts. The model was empirically tested, and data obtained from 116 respondents were subjected to factor and correlation analysis to explore the dimensionality of the retention construct. Research results support that retention is multidimensional and highlights the limitations of research that measure single factors related to retention. The model postulates that retention is the result of a good working relationship, service satisfaction, respect and support, clear terms of engagement; and affective conflict resolution. Insight into the nuances of each of these antecedents is also offered. In management practice, this model will provide valuable insight to agencies with regard to client retention management. Findings of this study may also be extended to other high-value professional service industries.
Keywords: 650